Female leadership styles and organizational commitment:A test on Sibu manufacturing companies - Hii, Hiong Ling. (Universiti Malaysia Sarawak (UNIMAS), 2013)
The general objective of this study was to investigate the effect of transformational leadership and transactional leadership on organizational commitment of manufacturing industry in Sibu, Sarawak. The present research differs from the previous studies whereby the study's framework has allowed for a better understanding on these relationships.